Balanced scorecards: Proposed framework for application at the local system level insights from international experiences - Mohamed Sayed Abdel Hamied; Ayman Elbagoury (Review of Economics and Political Science (REPS), 2025)
Purpose - The study aims to provide a clear framework of steps on how to implement the balanced scorecard model at the level of measuring and managing local performance, with a mix between what theoretical approaches show in this matter and examples of applied experiences in different contexts. Design/methodology/approach - The study relies on the case study approach, which was used to present pioneer experiences in the field of application of the model on local government's level, namely, in the USA, England and South Africa. This paper was done by reviewing the original balanced scorecard literature and writings regarding the public and local government sector. This literature formed the basis for analyzing the various sections of study. Findings - Balanced scorecard is one of the important models for developing and measuring local performance. International experiences under study confirmed that application of the model requires the following: The availability of bureaucratic will at the local level to apply the model, necessity of capacity building of local government units to apply it, introduction of institutional and strategic changes to the local units to be able to build their own performance cards, as well as strengthening local information systems, and not standardizing the performance cards at the different local administrative units. Originality/value - This study will be useful for scholars, policymakers and local executive leaders on ways to apply the balanced scorecards at the local government units.
Keywords: 330; Balanced scorecards (BSCs); Local councils; Local government; Performance; Strategy map